PENGEMBANGAN SISTEM INFORMASI DATA KONSUMEN DI PT. SNP FINANCE KOTA JAMBI: Information System Development, Consumer, Visual Basic 6.0 - -, Mulyadi (JURNAL AKADEMIKA, 2018)
Development of information systems is the unity of various elements that are interconnected in a place and have driving items such as objects, attributes, environment and internal relationships in the system. As for who explained about the development of information systems and the purpose of consumer data applications using Visual Basic 6.0 was created with the aim to facilitate consumer data collection. For employees of consumer data processing, especially in the Data Entry section, it will facilitate efficient data processing and facilitate the preparation of reports that will be given to the head of the company. The development of this information system uses visual basic 6.0 program and is supported by microsoft access 2007 as database management. For the development of data and information related to this research, it is obtained through field studies and literature study by looking for relevant sources and many things that need to be developed. In the future, with the entry of technology, it will be adjusted to better performance for application developers.